Heuristic UTD coefficients applied for the channel characterization in an andean scenario (2015)
This paper presents a comparison of three heuristic coefficients for the Uniform Theory of Diffraction (UTD), used to characterize the radiowave scattering in typical urban scenarios. The coefficients were implemented in a propagation model based on 3D ray-tracing techniques in an andean scenario. In order to evaluate each coefficient we analyze the statistical behavior of the mean and standard deviation of the absolute errors between the estimated values and the measured data of path loss in a large number of receptor points. Finally, we show the path loss prediction for each heuristic UTD coefficients proposed.